Homogeneous selection shapes rare biosphere in rhizosphere of medicinal plant. (October 2021) - Zhang, Guozhuang; Wei, Guangfei; Wei, Fugang; Chen, Zhongjian; He, Mingjun; Jiao, Shuo; Wang, Yong; Yu, Yuqi; Dong, Linlin; Chen, Shilin
Graphical abstract: Highlights: Homogeneous selection governs the assembly of rare biosphere in rhizosphere. Dispersal limitation dominates the assembly of abundant taxa in rhizosphere. Putative functions related to plant-microbe interaction were enriched in rare taxa. Abundant taxa located in more central positions in co-occurrence network. Abstract: Knowledge about the ecological patterns of abundant and rare bacteria in rhizosphere is still lacking. Through a large-scale sampling across the arable area of a medicinal plant Panax notoginseng, we examined the community assembly of abundant and rare rhizobacteria as well as their putative functions and co-occurrence patterns. At local level, the rare taxa exhibited significantly stronger phylogenetic clustering than the abundant taxa. At metacommunity level, both two subcommunities showed significant biogeographic patterns, but they were assembled by different ecological processes. Null model analysis showed that dispersal limitation (84.68%) governed the assembly of abundant subcommunity, whereas homogeneous selection (90.11%) dominated the dynamics of rare subcommunity. Although the putative functions indicated that the rare taxa potentially enriched more functional traits associated with plant-microbe interactions, the overall abundance profiles of putative pathways in two subcommunities exhibited significant collinearity. Additionally, the topological properties of abundant taxa in the co-occurrence network were significantly higher than those of rare taxa. We propose that stochasticity and determinism dominate the assembly of abundant and rare subcommunities, respectively. The abundant taxa may exhibit stronger environmental adaptability, while the rare taxa are more likely the result of rhizosphere effect. These findings also emphasize the importance of integrating phylogeny in ecological researches on plant-associated microbiota.